The Effectiveness Of Bamboo Dancing Technique To Improve Students Speaking Skill - Puput Aryanti; Sofyan A. Gani; Diana Achmad (Research in English and Education Journal, 2021)
Speaking is a verbal skill that plays an important role in language learning. However, during the internship, the writer found that the students faced some difficultiesin speaking English. Bamboo dancing technique is one of cooperative learning methods that is said to be effective in teaching speaking. Thus, the writer was eager to conduct a library study on the effectiveness of bamboo dancing in improving students’ speaking skill. Previous studies on bamboo dancing technique are the primary data for the writer to determine the effectiveness of the technique. The writer took five sources to be used as references, namely; Suprijono (2010), Ma’ruf Rahim (2013), Wahyuni (2015), Pitanto (2016), and IsnaeniNurdiawati (2017). The result of this study indicates that bamboo dancing technique is effective in improving students’ speaking skill. The result is supported by the data from the classroom observation, the questionnaire, and the students’ mean score of the previous studies. As bamboo dancing technique may take some time to complete, it is better applied in a small class. The next study on bamboo dancing technique should investigate the appropriate application of the technique itself. To conclude, bamboo dancing technique is effective to improve students’ achievement in speaking skill and to help teachers in creating a fun learning environment.